From the mechanics of obstacle avoidance towards the prevention of falls (Tijdschrift voor Gerontologie en Geriatrie, 2024)
Vivian GM Weerdesteyn. From the mechanics of obstacle avoidance towards the prevention of falls. Nijmegen: Colophon, 2005. 134 p. ISBN 9090198393